United States Census of Mortality: 1850, 1860, and 1870 - Fogel, Robert W. ([Verlag nicht ermittelbar], 2000)
This data collection is a portion of the historical data collected by the project, "Early Indicators of Later Work Levels, Disease, and Death," which is collecting military, medical, and socioeconomic data on a sample of white males mustered into the Union Army during the Civil War. During 1850, 1860, and 1870, mortality information was gathered at the county level as an addendum to the population census. These data examine the impact of environmental factors on life outcomes and look at the influence of infectious disease rates on economic and health patterns at late ages. Part 1, Disease Data, looks at cause of death from 66 disease classifications. Part 2, General Disease Data, also examines cause of death but through 18 broad disease categories. Variables included in both parts are state, county, year of death, and frequency of death by disease.